THE RELATIONSHIP OF HUSBAND AUTHORITY TO THE WIFE POLITICAL RIGHTS - Yana Suryana (Justitia et Pax, 2022)
This research aimed to show the relationship of husband authority in the form of intervention on wife political rights. The collection of data was carried out through interviews, observations, and literature studies in order to help answering the research questions. The results showed that the husband intervened in his wife's political rights. This was what escaped the attention of governments and gender drivers in protecting the political rights of wives. So far, the government has not maximally protected the rights of wives in the public sphere. Whereas the private/family institution is the root of the wife's political rights being unprotected. Thus, the family institution becomes the first place to lose the wife's independence in obtaining her political rights.